Politeness Comments on the Fizzo Reading App - Irmayani; Syarifah Lubna (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to describe the form of language politeness in the comments of Fizzo digital reading application users-based on Leech's maximal theory of politeness. Using a descriptive qualitative approach with pragmatic theory, data was obtained from comments on popular novels by exclusive authors (star writers). The results of the analysis showed that most of the comments reflected adherence to the principles of politeness, such as the maxim of wisdom, generosity, appreciation, simplicity, compatibility, and sympathy. However, it was also found that there were violations of the maxim which were generally triggered by dissatisfaction with the storyline. These findings confirm the importance of applying politeness in digital communication, as well as its potential as a teaching material to form ethical language competence in the technological era.